The Role of Interpersonal Communication in The Family: (Literature Review to Minimize Divorce Cases) - Siti Isnaeni (Commsphere: Jurnal Ilmu Komunikasi, 2025)
One of the strong bonds resulting from a sustainable relationship between individuals is marriage. However, along the way, commitment in marriage is often accompanied by challenges and problems that often occur. Even if this situation cannot be adequately resolved, it has the potential for a divorce rate that continues to increase. Referring to data from the Central Statistics Agency (BPS) of Indonesia in 2024 explains that 408,347 cases continued to emerge and were spread across several major cities, such as West Java, East Java, Central Java, North Sumatra, and DKI Jakarta. So, it can seriously impact other family members, from children to closest relatives. Ironically, some of the adverse effects that arise can be in the form of trauma, inhibited emotional development and drastic changes in a person's mood. This study aims to analyze the role of interpersonal communication in the family in more depth. Using a descriptive qualitative method, the study results show that a concrete strategy is needed to optimise family life, one of which is the openness of communication. That way, divorce cases can be minimized to create a comfortable environment and form a positive mindset for children. Keywords: Interpersonal Communication, Family, Divorce, Marriage